The indwelling of the Holy Spirit, pt 1: an evaluation of contemporary pneumatology - Engelbrecht, Ben (Journal of Theology for Southern Africa, 1980)
The rediscovery of the doctrine of the Holy Spirit in the second half of the twentieth century shows the following characteristics: 1) it aims at the interpretation of world experience as God-experience; 2) it does not draw a clear line of distinction between the immanence of the Spirit in creation, and his indwelling as a result of his outpouring on the day of Pentecost; 3) it interprets the work of the Spirit as a direct continuation of the work of Christ; 4) it limits the work of the spirit to a recognizable history of salvation; 5) it does not see the totality of history as the (pneumatic) first fruits of God's Kingdom; and 6) it fails to elaborate the significance of the Ascension for a theology of the world.
Keywords: Experience (Religion); History – Religious aspects; Holy Spirit; Trinity